Sexual violence against women: nursing care in health units (Research, Society and Development, 2023)
This article aims to describe nursing care for women victims of sexual violence in health units. This is an integrative literature review with a descriptive character, with a qualitative approach, carried out in the Virtual Health Library (BVS), LILACS and SCIELO, using the descriptors “Nursing”, “Nursing Assistance”, “Sexual violence” and “Violence against women” with the Boolean operators “AND and OR”. After applying inclusion and exclusion criteria, 16 articles published in the period from 2017 to 2022 were selected. The results found were listed in a table format in chronological order for a better approach to the discussion, where reception, humanized care and qualified listening were highlighted as the main activities of the nursing team. It is concluded that nursing was presented as a protagonist in the care of women victims of violence, and must be prepared for this, in turn, the lack of specific knowledge and studies focused on the subject in question, still point out as difficulties in the care of victims of sexual violence.